The role of financial development in reducing income inequality in selected Asian countries - Wang, Yujue; Mazlan, Nur Syazwani; Wan Ngah, Wan Azman Saini; Faheem, Muhammad (Center for Economic Integration, 2024)
The present study investigated the effects of financial development on income inequality for three income level groups across 12 Asian countries (areas) from 1980-2020. The three groups comprised countries with low, moderate, and high economic development. Using the Quantile-on-Quantile (QQ) approach, The findings showed that the impact of financial development on income inequality differed across the income level groups of the 12 selected Asian countries. The results suggested that financial development exacerbated income inequality in underdeveloped countries, while for moderately developed countries, financial development promoted income equality. Except for South Korea, the other countries in the high economic development group showed that financial development exacerbated income inequality. Therefore, the impact of financial development on income should be examined by groups, in which moderately-developed countries could devote more attention to promoting income equality through reforms focusing on the development of financial diversification and the enhancement of financial depth.